Cultural linguistics : cultural conceptualisations and language - Sharifian, Farzad (Cognitive linguistic studies in cultural contexts, 2017)
This ground-breaking book marks a milestone in the history of the newly developed field of Cultural Linguistics, a multidisciplinary area of research that explores the relationship between language and cultural conceptualisations. The most authoritative book in the field to date, it outlines the theoretical and analytical framework of Cultural Linguistics, elaborating on its key theoretical/analytical notions of cultural cognition, cultural schema, cultural category, and cultural metaphor. In addition, it brings to light a wide array of cultural conceptualisations drawn from many different languages and language varieties. The book reveals how the analytical tools of Cultural Linguistics can produce in-depth and insightful investigations into the cultural grounding of language in several domains and subdisciplines, including embodiment, emotion, religion, World Englishes, pragmatics, intercultural communication, Teaching English as an International Language (TEIL), and political discourse analysis. By presenting a comprehensive survey of recent research in Cultural Linguistics, this book demonstrates the relevance of the cultural conceptualisations encoded in language to all aspects of human life, from the very conceptualisations of life and death, to conceptualisations of emotion, body, humour, religion, gender, kinship, ageing, marriage, and politics. This book, in short, is a must-have reference work for scholars and students interested in Cultural Linguistics.